Effect of warming gown use on shivering and body temperature in chronic kidney disease patients undergoing hemodialysis via catheter - Anggraeni, Novita; Saryono, Saryono; Upoyo, Arif Setyo (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Haemodialysis is often accompanied by shivering, especially in patients with catheter access, which can reduce comfort, impair treatment efficacy, increase the risk of complications and contribute to inadequate dialysis. Addressing this issue through non-pharmacological means, such as a warming gown, offers a potentially effective, safe, and economical solution to improve patient outcomes. Purpose: To develop a warming gown as an innovation to reduce the incidence of shivering in chronic kidney disease patients undergoing haemodialysis with a haemodialysis catheter. Methods: This study employed a two-stage Research and Development design. In the first stage, a reusable, adaptive warming gown for HD catheter patients was developed and validated (S-CVI/Ave = 0.99). Second, a quasi-experiment was conducted with 60 patients recruited through total sampling. Subsequently, patients were randomly allocated to either the intervention group (warming gown) or the control group (blanket) using computer-generated randomisation based on their identification numbers. Shivering (Crossley and Mahajan scale) and body temperature (digital thermometer) were measured at 0, 15, 30, 60, and 120 minutes. Data were analysed using Wilcoxon, Friedman, and Bonferroni-corrected repeated Mann–Whitney tests. Results: The intervention group showed a significant reduction in shivering levels from 2.63 ± 1.27 to 0.37 ± 0.49 (p < 0.001) and an increase in body temperature from 36.36 ± 0.52 to 36.84 ± 0.29 (p < 0.001). In contrast, the control group showed no significant changes (p > 0.05). Conclusions: The warming gown was proven effective in reducing shivering and increasing body temperature in haemodialysis patients, offering advantages in comfort, safety, and cost efficiency.